Onomastics in Contemporary Public Space. - Felecan, Oliviu (Cambridge Scholars Publishing, 2013)
Onomastics in Contemporary Public Space aims at analysing names and name-giving from an intercultural perspective, within the context of contemporary public space. As was the case of Name and Naming: Synchronic and Diachronic Perspectives (Cambridge Scholars Publishing, 2012), the geographical areas investigated in the studies included in this volume are very diverse, referring not only to European cultural space, but also to American, Asian, African and Australian contexts. Being a collectiv ...